1996
DOI: 10.1007/bf03172945
|View full text |Cite
|
Sign up to set email alerts
|

Verbal discussions about social problem-solving between friends and non-friends

Abstract: In the field of developmental social psychology there is a consensus concerning the social nature of intelligence. In spite of the important empirical investigations in this field over the last fifteen years, the influence of the quality of a relationship on joint problem-solving and learning is still poorly understood. This explorary study investigated the influence of socio-affective context on the interactive modalities surrounding social problem-solving discussions conducted with 32 dyads of8-year-old Swis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…Il découle de ces recherches une deuxième proposition qui étend le domaine du conflit sociocognitif : des régulations de nature sociale (normes, conventions, représentations, règles sociales familières, contrat) qui régissent une interaction donnée peuvent aussi engendrer de nouvelles coordinations cognitives. 3) Des travaux plus récents ont pris en considération le rôle des significations sociales en jeu dans l'histoire relationnelle des partenaires en interaction, en supposant que la nature de la relation entre deux individus surdétermine la gestion cognitive de la tâche à effectuer, en affectant les processus cognitifs mis en oeuvre par la dyade (Bensalah, 1995 ;Dumont & Moss, 1996 ;Sorsana, 1996Sorsana, , 1997Sorsana, , 1999b. Ainsi, une troisième proposition prolonge les études du conflit sociocognitif : la nature (positive ou négative) des relations entre enfants joue un rôle dans la façon dont les sujets gèrent cognitivement et socialement la résolution d'une tâche.…”
unclassified
“…Il découle de ces recherches une deuxième proposition qui étend le domaine du conflit sociocognitif : des régulations de nature sociale (normes, conventions, représentations, règles sociales familières, contrat) qui régissent une interaction donnée peuvent aussi engendrer de nouvelles coordinations cognitives. 3) Des travaux plus récents ont pris en considération le rôle des significations sociales en jeu dans l'histoire relationnelle des partenaires en interaction, en supposant que la nature de la relation entre deux individus surdétermine la gestion cognitive de la tâche à effectuer, en affectant les processus cognitifs mis en oeuvre par la dyade (Bensalah, 1995 ;Dumont & Moss, 1996 ;Sorsana, 1996Sorsana, , 1997Sorsana, , 1999b. Ainsi, une troisième proposition prolonge les études du conflit sociocognitif : la nature (positive ou négative) des relations entre enfants joue un rôle dans la façon dont les sujets gèrent cognitivement et socialement la résolution d'une tâche.…”
unclassified
“…They observed that the nature of the relationship shared between partners -positive relationship versus negative one -overdetermined the cognitive management of tasks, by affecting the cognitive processes used by the dyad: children in 'friend' dyads had more exchanges which were more elaborate and more critical than children in 'not-friends' or 'indifferent' dyads; they interacted in a cordial work environment (laughter, exclamations, teasing) characterized by reciprocity of exchanges, and they were more attentive, more respectful, and more demanding of each other. All of these are behaviors that allowed them to take their partner's suggestions into account [Bukowski, Newcomb, & Hartup, 1996;Dumont & Moss, 1996;Kutnick & Kington, 2005;Nelson & Aboud, 1985;Newcomb & Bagwell, 1995;Sorsana & Musiol, 2005].As Psaltis et al [2009] pointed out, this 'second generation of studies' -an expression that we can extend to all research of this period (including non-Swiss research) -granted a more institutionalized role to social variables: the task is not only an activity that a child carries out with two or three partners (if we include the presence of the experimenter). To solve it, children use the set of social parameters related to it.…”
mentioning
confidence: 99%